Dampak dari Transportasi Bagi Perekonomian Nusa Penida: Serta Pengelolaan Destinasi Wisata - Purnamawati, Ida Ayu Putu Santi; Laksmi, Putu Ayu Sita (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2025)
The aim of this research is to determine the impact of maritime transportation on the economy of Nusa Penida, as well as the management of tourism destinations on the local community and surrounding environment of Nusa Penida. The indicators of this study are the positive and negative impacts of tourism in Nusa Penida. The sampling technique includes cluster sampling or area sampling. Data were collected from 100 respondents and analyzed using qualitative descriptive methods and Likert scale analysis. The findings indicate that the presence of transportation on Nusa Penida Island has a significant positive impact with an overall average score of 2.85 based on community perceptions, meaning that the presence of transportation has a positive influence. However, there are also negative impacts on the environment, with an average score of 2.32, indicating that transportation on Nusa Penida has a negative impact on the environment, leading to a decline in environmental quality